Paradigma Oposisi dan Prinsip Check and Balances dalam Sistem Ketatanegaraan di Indonesia - Indra Budi Jaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Opposition is an important element in a democratic system that functions as a mechanism of control over power. In the context of Indonesian constitutionality, the existence of the opposition is a prerequisite for the realization of a healthy and effective democracy. However, in practice, the term opposition is often equated with the principle of checks and balances, thus causing a blur of meaning between the two. This paper aims to examine the paradigm of the opposition in the Pancasila democratic system and analyze the relationship between the opposition and the principle of checks and balances in the Indonesian constitutional system. This research uses a qualitative method with a normative juridical approach, through a conceptual approach and a legislative approach. An analysis was carried out on the doctrines of constitutional law and provisions in the 1945 Constitution of the Republic of Indonesia related to the implementation of opposition and the principle of checks and balances. This approach was chosen to explore legal issues in depth and find a comprehensive understanding of the role of the opposition in the Indonesian constitutional system. The results of the study show that even though Indonesia does not adhere to a parliamentary or presidential system with two parties, the implementation of the opposition is still relevant and carried out with attention to the values of consensus in Pancasila democracy. The opposition in Indonesia is not confrontational, but constructive and oriented towards strengthening the system of supervision of power. Opposition and the principle of checks and balances are two concepts that are terminologically different, but interrelated and inseparable in Indonesian constitutional practice. Both serve as important instruments in maintaining the balance of power and ensuring accountability in the administration of government. Thus, a proper understanding of the opposition paradigm and the principle of checks and balances is the key to strengthening constitutional democracy in Indonesia.